DOES SCAFFOLDING HELP STUDENTS TO WRITE BETTER? - Yunik Susanti (Universitas PGRI Madiun, 2014)
Learning to write is a difficult and complex series of processes that require a range of explicit teaching methodologies throughout all the stages of learning. The capacity of teacher to create positive classroom atmosphere and using appropriate teaching technique will help students to attain the goal of writing. This pre-experimental research aims to measure the effectiveness of scaffolding technique to the students writing ability. The result of the data analysis shows that the mean score of pre-test and post-test are 58. 87 and 71. 29 . Then the t-score is 4. 45 and the t-table at the degree of significant 5% is 2. 042, so the t-score 4. 45 is higher than the t-table. It means very significant, thus scaffolding technique is effective to be used in teaching writing as it helps the students to write better. This result supports the proposed theory which stated that scaffolding helps the students to write by providing a support structure to enable certain activities and skills to develop lies on the frameworks used by the teacher, giving the actual carrying out of particular activities in class, also there is the assistance provided in moment-to-moment interaction among students and teacher.